The Influence of Gadgets on the Morals of Teenagers in Sarolangun Jambi Province - Darmawi Darmawi; Saman Kamaludin; Nani Angraini; Suparno Suparno; Oktawini Ofiani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The development of information technology has had a significant impact on the lives of adolescents, including in Sarolangun Regency, Jambi Province. The massive use of gadgets affects various aspects of adolescent life, one of which is morality because morality is a person's behavior or attitude that arises from within, which is based on moral and ethical values. This article aims to analyze the influence of gadget use on adolescent morality in Sarolangun using a qualitative descriptive approach. Data were collected through literature studies from various journals, mass media, and academic books. The results of the analysis show that gadget use has both positive and negative influences on adolescent morality in Sarolangun, Jambi Province. Positive influences include access to educational information and the development of digital skills as well as facilitating access to lessons, while negative influences include decreased social interaction, increased aggressive behavior, and decreased compliance with social norms regarding parents and prevailing social norms in society. This requires the active role of parents, educators, and the community in guiding the wise use of gadgets to shape adolescent morality that is good and beneficial for themselves and society.